(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This research focuses on the production of concrete with possible use of agricultural and industrial wastes in combined form as replacement to OPC along with use of waste rubber tire granules as coarse aggregate. The primary objective of this research is to is to check possible use of ternary blend rubcrete in non- structural uses like pavements. In this research the optimum proportion of combined ternary mix (FA, SF, RHA) as partial replacement of binder/cement in natural aggregate concrete of M35 grade among the selected proportions were evaluated at the end of 7 and 28 days. Among the various proportions, the optimum combined proportion was found to be 40% replacement (10%SF, 10%RHA & 20%FA). The natural coarse aggregates (NA) of the optimum ternary blend were further replaced with waste tire granules (in proportions of 20%, 30% and 40%) and examined at end of 7 and 28 days. The optimum proportion of rubber (RA) in ternary blend rubcrete was found to be 20% as values above this percentage showed tremendous decrease in strength. Detailed experimental study of the fresh concrete property (workability) was performed & the compressive strength, flexural strength tests were carried out at the end of 7 and 28 days. Also, water absorption and loss in weight due to acid attack was examined at the end of 28 days. It is followed by SEM analysis and XRD analysis of the optimum proportions in comparison to control mix which justifies the results of this research. This research paves the way towards sustainable, cost efficient and environment friendly construction.